DOPPLER ULTRASOUND IN LIVER CIRRHOSIS: CORRELATION OF HEPATIC ARTERY AND PORTAL VEIN MEASUREMENTS WITH MODEL FOR END‐STAGE LIVER DISEASE SCORE (The Research of Medical Science Review, 2025)
OBJECTIVE: To evaluate the correlation between Doppler ultrasound measurements of the hepatic artery and portal vein with the Model for End-Stage Liver Disease (MELD) score in patients with liver cirrhosis. METHODOLOGY: This cross-sectional investigation was executed at the Department of Radiology, Sindh Police Hospital, Karachi, encompassing a cohort of 103 cirrhotic patients who were recruited through a non-probability consecutive sampling methodology. Doppler ultrasonography was employed to quantify the velocities of the hepatic artery and portal vein, in addition to the computation of the hepatic arterial resistive index. The Model for End-Stage Liver Disease (MELD) scores were derived from serum bilirubin, creatinine, and International Normalized Ratio (INR) values. A Pearson correlation analysis was conducted utilizing SPSS version 26 to evaluate the interrelationship between the Doppler parameters and the MELD scores. RESULTS: There were 103 participants having a mean age of 50.51 ± 12.35 years with 66% males and 34% females. The mean hepatic artery velocity was 84.93 ± 56.80, showing a strong positive correlation (r = 0.933, p = 0.000) with the MELD score. Similarly, the portal vein velocity had a mean of 17.84 ± 5.76 and also showed a strong positive correlation (r=0.883, p=0.000) with the MELD score. CONCLUSION: This investigation elucidated a robust positive correlation between Doppler ultrasound measurements of the hepatic artery and portal vein with the Model for End-Stage Liver Disease (MELD) score in individuals aflicted with liver cirrhosis. The amalgamation of Doppler parameters alongside MELD scoring has the potential to enhance risk stratification, enable prompt clinical interventions, and aid in the prioritization of candidates for liver transplantation. Future multicenter studies with larger sample size are necessary to validate these results and to formulate standardized protocols for Doppler-based monitoring.